PENGARUH STRUKTUR MODAL, STRUKTUR KEPEMILIKAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN SEKTOR PROPERTI, REAL ESTATE DAN KONSTRUKSI BANGUNAN - Romi Ferdian (FEBI UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this study was to examine the effect of capital structure, ownership structure and dividend policy on company values. This is a causal associative-research. The population of this study consisted of 63 companies engaged in the property, real estate and building construction sectors and listed in the Indonesia Stock Exchange during 2017-2021. The samples were selected using non-probability purposive sampling since the selection required certain considerations. The data were analyzed using Ordinary Least Square (OLS) panel data regression of EViews 9. The results of the study revealed that the capital structure variable has positive and significant effects on the company values. This is shown by the regression coefficient value on the t test of 2.358820 and the significance level of 0.0200 > 0.05. Similarly, the ownership structure variable has positive and significant effect on the company values with regression coefficient value of the t test of 4.610279 and the significance level of 0.000 > 0.05. Meanwhile, the dividend policy variable has no significant effect on the company values since the regression coefficient on the t count is 1.475912 and at a significance level of 0.1427 > 0.05.